The International Committee of the Red Cross and Civil Rights (Part I) - S. Sayapin (Московский журнал международного права, 2012)
Throughout a considerable part of its history, the International Committee of the Red Cross (ICRC) has customarily refrained from invoking international human rights law, for reason of this law’s alleged politicisation. However, the changing character of armed conflicts and other situations of violence where the ICRC is currently operating have prompted it to set a framework for making some limited use of selected and applicable human rights, for the purpose of reinforcing the protection and assistance it provides. This article examines the norms of international law representing civil rights, which the ICRC may invoke in its humanitarian action, as well as the conditions for their invocation in the ICRC practice.